STATE EFFORTS IN FULFILLING THE CIVIL RIGHTS OF THE SUNDA WIWITAN BADUY INDIGENOUS COMMUNITY AFTER THE MK DECISION NO.97/PUU-XIV/2016 - Rafi Drajat, Muhammad Rifqi; Rahmawati, Tiara (Universitas Islam Negeri Ar-Raniry, 2024)
The strength of the customary law adhered to by the Baduy traditional community comes from internal factors originating from the characteristics of the community itself, which believes in the values contained in its customary law. The implementation of the fulfillment of civil rights following the Constitutional Court decision NO.97/PUU-XIV/2016 has not been fully felt by the Baduy community, one of which is in the process of registering marriages, where until now marriage registration is still only recorded in marriage certificates issued from the village. In writing this article, research methods were used with primary and secondary data collection. The results of the research show that the State's efforts to fulfill the civil rights of believers in Indonesia have been implemented with the Constitutional Court Decision Number 97/2016 as a first step in eliminating discrimination in population registration, but its implementation requires different methods in each region and region, especially for the community. adherents of the Sundanese Wiwitan Baduy belief who strongly maintain the traditions and messages of their ancestors. As for Regional Regulation no. 8 of 2015 concerning Recognition, Protection and Empowerment of the Kasepuhan Customary Law Community, which is proof that the existence of the Baduy customary law community is actually recognized by the State.